(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Glaucoma is one of the global public health problems. This disease is one of the main causes of irreversible blindness worldwide. Despite progress in therapy and increased effectiveness of methods and measures to reduce intraocular pressure (IOP) and surgical methods, the disease remains poorly controlled due to asymptomatic course in the early stages and poor coverage of early diagnosis, especially in countries with poorly developed economies. According to WHO, in 2020, glaucoma caused blindness in 3.61 million people and severe visual impairment in 4.14 million, especially in people over 50 years of age. Given that glaucoma is incurable but potentially controllable, early diagnosis and neuroprotective strategies aimed at preserving the optic nerve are of particular importance. Scientific novelty: This article is devoted to the analysis of modern approaches to neuroprotection in glaucoma, issues of early diagnostics and the potential for integrating these areas into public health strategies. If glaucoma is considered not only as an ophthalmological but also as a neurodegenerative disease based on multifactorial death of retinal ganglion cells (RGC), this shifts the emphasis from exclusively hypotensive therapy to the need for neuroprotective strategies, which reflects the modern vector in the pathogenesis and treatment of glaucoma. A conclusion is made about the relevance of developing and implementing neuroprotection methods and in-depth screening to improve the effectiveness of combating glaucoma at early stages. The need for a combined approach to treatment adapted to the molecular mechanisms of damage in a particular patient is substantiated, which corresponds to the modern paradigm of personalized medicine.